Environmental and Hydrological Changes of Lake Coatetelco in Central Mesoamerica (Southwest Mexico) Over the Holocene and Comparison With Climatic Forcing - García-Arriola, Oscar Agesandro; Roy, Priyadarsi D.; Vargas-Martínez, Irma Gabriela; Giron-García, Ma. Patricia; Curtis, Jason H.; Israde-Alcantara, Isabel; Quiroz-Jimenez, Jesús David (Frontiers in Ecology and Evolution, 2022)
Elemental composition of inorganic fraction, and carbon isotopes and C/N of organic matter from a new radiocarbon-dated sedimentary sequence collected from the Lake Coatetelco (960 m asl) extended information about the environmental and hydrological conditions of central Mesoamerica from the earliest Holocene to the interval of first human settlements in the lake vicinity and nearby streams. Proxy-based reconstructions of erosion/runoff (Ti), water column salinity (CaCO3), sediment-water interactions (PIA) and provenance of organics (δ13Corg and C/N) showed similarities with the summer insolation modulated ITCZ position between ~11.5-4.2 cal ka BP, and more frequent ENSO between ~4.2-2.1 cal ka BP. After a possible depositional hiatus between ~11.2-10.2 cal ka BP, the moderate-to-extremely altered sediments were deposited with enhanced erosion/runoff during the wetter ~10.2-6 cal ka BP and the organic matter was dominantly autochthonous. Comparison of δ13Corg and C/N suggested that the contribution of C4 plants to organic matter increased over the drier ~6-4.2 cal ka BP. Sediments representing this middle-Holocene drought-like conditions showed geochemical similarity with sediments of the Post-Classic drought (~1-0.4 cal ka BP), coeval with abandonment of the Xochicalco culture. Variation in seasonal insolation in orbital-scale might have forced frequent droughts between ~6-4.2 cal ka BP and the ENSO related short-lived storms possibly led to an unstable hydroclimate after ~4.2 cal ka BP when the first Olmec settlements commenced in the region. Dissimilarity between this lacustrine archive and speleothems from the southwest Mexico for later part of the Holocene reflected different sensitivities of the geological records to seasonal-and-annual precipitation.